Pelatihan Pembelajaran yang Efektif untuk Mahasiswa - Suwinto Johan; Novia Clarista Mulyanto; Jovanka Andira Sarwoto (Unika Santu Paulus Ruteng, 2023)
The learning process between schools and universities is a different learning process. When in school, a student has sufficient study time and is always reminded by the teacher and homeroom teacher. However, when a student becomes a student, the pattern of learning becomes different. A student is required to be able to take responsibility for himself, including in the learning process. If the student does not pass one course, then the student must repeat. This is different from learning in high school. Lecturers will not remind students to study. A student who does not pass a course must repeat the course in the next semester. Meanwhile, a student who does not pass, can still go to class, with the consideration of the homeroom teacher. Students will look for effective ways of learning when entering the campus world. This effective way of learning is very necessary for a successful student. This community service activity aims to share effective learning activities for students. An effective learning pattern starts from the learning objectives, preparation and implementation of the learning process. The implementation of this learning process starts from the ability to listen, focus and take notes and practice questions. Independent learning by students. Exams can come from lecture materials, but can also come from related materials. Thus, a student will be able to learn effectively. A student must be able to study independently